INVESTIGATING THE POST-PURCHASE REGRET OF CONSUMERS IN MANADO - Masinambow, Chriskendry H.; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: The post-purchase regret of a consumer is one of the reactions that most influence almost all of the form of consumer behavior towards any kind of product they purchased, in this study, the main focus of type of product is the most daily usage product of the consumer. In term of marketing, which is one of the important part of the company, and which the product that produced from the producer or the seller themselves could be exposed to the consumer, the post-purchase regret is one of the factor that had been an important matter for the marketer to put in their agenda and composing better strategies or tactics of selling a product to the consumers and the customers. In this research, the study aim to find out and investigates how is the post-purchase regret of the consumer?s most used and bought product. The researcher used a purposive sampling as a sampling technique to conduct the research. And the result of this study shows how strong the comparison factor between the products of consumer?s usage as seemingly the most described factor among other indicators. Also it is important for marketer to find a better or unique ways in order to promote the product, or for producer to develop the trials and experiment of the product. The recommendations proposed from this study is better for a company to review the finished product in term of better quality and more sensible, affordable price before the product is sent out to the market. Keywords: post-purchase regret, consumers